Comprehensive review of medicinal plant Nauclea orientalis (L.) - Vinotha, S.; Thuvaragan, S. (Herba Polonica, 2026)
Due to their minimal adverse effects, approximately 21,000 plant species were employed for medicinal purposes globally. Medicinal plants are regarded as a plethora of natural constituents that can be utilized as nutraceuticals and developed into synthetic drugs to enhance health. Nauclea orientalis (L.) L. (Rubiaceae family), a plant that is indigenous to Australia, India, Sri Lanka, Thailand, the Philippines, Indonesia, and other countries, is utilized in the Indigenous Medical Sector to treat a diverse array of ailments due to its high alkaloid content. In order to provide a comprehensive overview of this multifunctional plant, the classification, habitat, medicinal applications, chemical constituents, phytochemical and physicochemical properties, and diverse pharmacological activities of its parts have been examined. Moreover, this review article establishes a scientific foundation that can be used to conduct future research in order to develop nutraceuticals from this plant.
Keywords: Medicinal plant; Nauclea orientalis; Pharmacological and phytochemical review; Rubiaceae